The Rоle of Teаchers in Germаn Lаnguаge Teаching fоr Motivаting and Guiding Lаnguаge Leаrners - Xamidovna, Nuritdinova Shoira; Yusupovich, Ibragimov Vakhobjon (European Journal of Life Safety and Stability (2660-9630), 2022)
In the article were analyzed the role of teachers in German language teaching for motivating and guiding language learners.